Cul-De-Sac - Fielding, Joy (New York : Ballantine Books, 2021)
"A shooting lays bare the secrets harbored by five families in a sleepy suburban cul-de-sac in this riveting psychological thriller from the New York Times bestselling author of All the Wrong Places"--.
Keywords: Suspense fiction; Mystery; Suspense fiction; Psychological fiction